Backward-Sloping Labor Supply Functions in Dual Economies–The Africa Case: Comment - McLoughlin, Peter F. M. (Quarterly Journal of Economics, 1962)
Journal Article Backward-Sloping Labor Supply Function in Dual Economies — the Africa Case: Comment Get access Peter F. M. McLoughlin Peter F. M. McLoughlin University op California, Los Angeles Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 76, Issue 4, December 1962, Pages 660–662, https://doi.org/10.2307/1879553 Published: 01 December 1962